Small Batch Manufacturing in the Age of Disruption to Reduce Slow Moving, Obsolete and Deteriorating Finished Goods in Fast Moving Consumer Goods Industry - Anthony Vaz; Anwar Tedjamulja; Rajendran Narayanasamy (International Journal of Supply Chain Management, 2022)
The fast-moving consumer goods (FMCG) industry is characterised by many stock keeping units being held in hypermarkets, supermarkets, minimarkets, convenience stores, smaller sundry shops as well as in centralised or decentralised warehouses supplied from batch manufacturing. In the process of manufacturing and distributing a large range of items, a portion of slow-moving items result in obsolete stocks being held. These slow-moving items often sit on shelves for long periods of time and upon reaching their expiry dates, some deteriorate too. In these circumstances, the supply chain manager may decide to dispose or write them off at a loss. This study aims to show how analysis of such inventory and their demand popularity could be used to install small batch capacity, applying a make to order policy in the FMCG industry for non-popular items. Supply chain managers may also transfer finished goods and moving single units of finished goods from an opened carton between retail outlets and warehouses before applying a make when zero policy to reduce and eliminate such waste in supply chains.